ZnO:InN oxynitride: A novel and unconventional photocatalyst for efficient UV–visible light driven hydrogen evolution from water. (October 2019) - Menon, Sumithra Sivadas; Hafeez, Hafeez Yusuf; Gupta, Bhavana; Baskar, K.; Bhalerao, Gopal; Hussain, Shamima; Neppolian, Bernaurdshaw; Singh, Shubra
Abstract: A novel UV–visible light active oxynitride photocatalyst, ZnO:InN, has been demostrated to exhibit efficient hydrogen evolution from water as compared to some conventional photocatalysts. A reduction in bandgap (2.82 eV), as estimated from diffuse reflectance spectra, is explained using Valence band XPS studies and attributed to the upshift in valence band maximum. Photocatalytic activity of the samples has been demonstrated by organic dye degradation, where 92% decay was observed in 180 min under direct sunlight. Photoelectrochemical studies under visible light showed significant photoresponse with a photocurrent density of ∼8 μA/cm 2 . This study, as per our knowledge, is first of its kind where ZnO:InN oxynitride has been explored as a UV–visible light active photocatalyst with significant H2 generation of ∼48 μmol/g by UV–visible light water splitting using methanol scavenger. The results show the promising future applications of ZnO:InN oxynitride as a sunlight active photocatalyst for hydrogen production. Highlights: Synthesis of novel Zn1-x Inx O1-y Ny oxynitride photocatalyst for H2 evolution. Bandgap modification to 2.82 eV. Methylene blue degradation upto 92% under direct sunlight. Significant Photocurrent generation under UV–Vis irradiation. Hydrogen evolution using Zn1-x Inx O1-y Ny oxynitride reported for first time.